Correlation and path coefficient analysis in fat and fatty acids of rapeseed and mustard (Bangladesh Journal of Agricultural Research, 2010)
Twenty-two genotypes of Brassica (B. rapa, B. juncea, and B. napus) were studied for correlation co-efficient between major fatty acids and path co-efficient analysis to partition the cause and effect relationship into direct and indirect components. Correlation coefficient of major fatty acids revealed that significant and positive correlation was between palmitic and oleic acids, palmitic and linoleic acids, palmitic and cicosenoic acids, oleic and eicosenoic acids, linoleic and linolenic acids and eicosenoic and erucic acids, while significant and negative correlation was observed between palmitic and erucic acids, stearic and linolenic acids and oleic and erucic acids. Path coefficient revealed that direct effect of all fatty acids except palmitic acid on oil content was positive. Indirect effect of erucic acid through all other fatty acids except palmitic acid on oil content was negative, Indirect effect of palmitic acid via all other fatty acids except erucic acid was positive. Key Words: Fat and fatty acids; Rapeseed; mustard. DOI: 10.3329/bjar.v34i2.5796Bangladesh J. Agril. Res. 34(2): 247-253, June 2009